A Comparative Pharmaceutical Study of Aranaladi Taila and Khajita Aranaladi Taila - Pillai, Rekhasree; Neethu, P; Sanila, V K (International Research Journal of Ayurveda & Yoga, 2023)
Introduction: Sneha Kalpana is a group of preparations of medicated ghrita (ghee) and taila (oils). The use of various Samskaras allows for the transformation of the properties of ingredients into the Sneha Dravya. One such samskara known by the name Manthana Samskara aids in the proper mixing of two substances as well as the incorporation of Sheeta Guna into the preparation and make it a homogenous mixture. This helps in improving the stability of the final preparation. Aranaladi taila mentioned in Sahasrayoga is an effective oil preparation for the treatment of Vatarakta associated with daha and jwara. Materials and Methods: In this study, pharmaceutical preparation of Aranaladi taila and Khajita Aranaladi taila was done as per Sahasrayoga reference. Aranaladi taila is prepared with tila taila as its base and it contains kanjika as dravadravya. This preparation also contains sarjarasa too. However, according to Sahasrayoga, Aranaladi taila can be converted to Khajita by adding a small amount of water and assisting in Manthana samskara. The present study is an attempt to compare the pharmaceutical aspect of Aranaladi taila and Khajita Aranaladi taila. Result: Aranaladi taila was obtained using 800 ml tila taila, 3200 ml kanji, and 182 g sarjarasa. To convert 20 0 ml of Aranaladi taila to khajita form, 100 ml of water was added little by little while churning. Discussion: Conversion of Aranaladi taila to its Khajita form imparts sheeta guna to the formulation thereby enhancing its pittahara property. Conclusion: This study examined the preparation of Aranaladi taila, as well as the time and water required to convert it to Khajita form.